THE COMMUNITY SATISFACTION TOWARDS THE PEACE AND ORDER PROGRAMS - Habiatan, Eric N. (International Journal of Psychosocial Rehabilitation, 2020)
This study examined the community satisfaction towards the peace and order programs of Cabagan, Isabela, Philippines. Specifically, the satisfaction levels of the urban and rural communities to the peace and order programs were scrutinized. A total of three hundred sixty four (364) community residents comprising one hundred seventeen (117) from the urban communities and two hundred forty seven (247) from the rural communities served as the respondents in this study. Descriptive design was used to analyze and interpret the data which were gathered through a validated and tested questionnaire. The findings revealed that the community residents of both the urban and rural communities are “moderately satisfied” with the peace and order programs. Furthermore, the result magnified that there is no significant difference between the satisfaction level of the urban and rural communities towards the peace and order programs. Finally, the findings signify that the peace and order programs content public safety and have evidently benefited the community.